CARDIOPROTECTIVE EFFECTS OF CURCUMA LONGA L - Bilovol, O.M.; Kniazkova, I.I.; Mishchenko, V.K.; Kuzminova, N.V.; Barbashova, V.O.; Molodan, D.V.; Abramova, L.P. (World of Medicine and Biology, 2025)
The purpose of the study was to analyze the literature on the phytochemistry and basic pharmacological properties that can realize the cardioprotective effect of Curcuma longa L and the results of experimental and clinical studies of its use for cardiovascular pathology. Curcumin is the main active ingredient of turmeric, which has a wide range of biological and pharmacological activities. The article presents an analysis of studies that have investigated the antioxidant, anti-inflammatory effects of curcumin and its influence on endothelial function and lipid metabolism. Curcumin’s molecular targets are diverse, ranging from transcription factors, growth factors and their receptors, cytokines and enzymes to proteins that regulate cell proliferation and apoptosis. Experimental studies show that curcumin has a positive effect on myocardial ischemia-reperfusion injury, helps to inhibit cardiomyocyte hypertrophy, myocardial fibrosis and ventricular remodeling, which emphasizes the feasibility of studying additional curcumin administration in heart failure to confirm and quantify its therapeutic effect.